2016
DOI: 10.1038/nn.4252
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent false neurotransmitter reveals functionally silent dopamine vesicle clusters in the striatum

Abstract: Neurotransmission at dopaminergic synapses has been studied with techniques that provide high temporal resolution but cannot resolve individual synapses. To elucidate the spatial dynamics and heterogeneity of individual dopamine boutons, we developed fluorescent false neurotransmitter 200 (FFN200), a vesicular monoamine transporter 2 (VMAT2) substrate that is the first probe to selectively trace monoamine exocytosis in both neuronal cell culture and brain tissue. By monitoring electrically-evoked Ca2+ transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
144
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(165 citation statements)
references
References 57 publications
(85 reference statements)
17
144
0
Order By: Relevance
“…Active zone-like release sites in dopamine neurons might be controlled similarly, for example by modification of RIM, to regulate dopamine signaling. Previous studies have found heterogeneity of dopamine release properties across varicosities, including variable p and silent varicosities (Cragg, 2003; Pereira et al, 2016). Variable composition or occurrence of release sites could be a tunable feature that contributes to these functional properties, and dopamine release could be regulated by activating or silencing entire vesicle clusters through adding or removing active zone-like sites.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Active zone-like release sites in dopamine neurons might be controlled similarly, for example by modification of RIM, to regulate dopamine signaling. Previous studies have found heterogeneity of dopamine release properties across varicosities, including variable p and silent varicosities (Cragg, 2003; Pereira et al, 2016). Variable composition or occurrence of release sites could be a tunable feature that contributes to these functional properties, and dopamine release could be regulated by activating or silencing entire vesicle clusters through adding or removing active zone-like sites.…”
Section: Discussionmentioning
confidence: 95%
“…Recent experiments suggest that only ~20% of dopamine varicosities release dopamine (Pereira et al, 2016), and a similar percentage of varicosities is associated with postsynaptic specializations (Cailld et al, 1996; Descarries et al, 1996; Yung et al, 1995). Remarkably, dopamine may also mediate relatively fast postsynaptic currents (Gantz et al, 2013; Marcott et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FFNs acting as VMAT2 substrates revealed the accumulation of neurotransmitters in both culture and acute brain slices. 28 FFNs are useful tools for studying the probing mechanisms of vesicular release at the single cell level, facilitating monitoring of partial fusion of neurotransmitters, such as kiss-and-run. However, the actual concentration of neurotransmitters in synaptic cleft is not detected using this method.…”
Section: Imagingmentioning
confidence: 99%
“…Fluorescent false neurotransmitters (FFNs) represent a class of cell specific imaging labels for visualizing monoamine neurotransmitter release [16, 17]. FFN200 (Figure 1), for instance, enters cells and gets enriched in the secretory granule of dopaminergic neurons by the vesicular monoamine transporter 2.…”
Section: Tagging Secretory Vesicles With Fluorescent Probes For Monitmentioning
confidence: 99%
“…FFN200 (Figure 1), for instance, enters cells and gets enriched in the secretory granule of dopaminergic neurons by the vesicular monoamine transporter 2. Subsequent cell activation released FFN200 from the labeled secretory granule, and the loss of FFN200 fluorescence signal from the granule was used as a surrogate marker of dopamine release [17]. The study revealed the prevalence of presynaptically silent synapses that showed little dopamine release despite a reliable Ca 2+ influx upon electrical stimulation, suggesting functional heterogeneity of dopamine release sites in the central nervous systems.…”
Section: Tagging Secretory Vesicles With Fluorescent Probes For Monitmentioning
confidence: 99%